The counseling needs for classroom teachers specialization in Jerash University from their point of view and its relationship with certain variables (Journal of the College of Education for Women, 2019)
This study aimed at identifying the counseling needs for classroom teachers specialization inJerash university. The sample of the study consisted (112) students. To achieve this goal ascale with (39) items was built by the researcher, this scale has four domains they are asfollows; family, social, psychological and academic domain. The results of this study showedthat counseling needs obtain the heighest average. As well as, the results of the study revealedthat there were statistical differences in favor of gender and teaching year variable. Finally thestudy stated a list of recommendations.